Anti-IgE therapy versus allergen-specific immunotherapy for food allergy: weighing the pros and cons - Kulis, Michael D.; Humphrey, Jessica R.; Krempski, James W.; Kim, Edwin H.; Smeekens, Johanna M. (Frontiers in Immunology, 2025)
With the recent FDA approval of the anti-IgE biologic, omalizumab, in 2024 for the treatment of food allergy, it is critical to consider the advantages and disadvantages of anti-IgE and allergen-specific immunotherapies (AITs) to help determine optimal patient care. Several AITs have been studied for food allergy, including oral (OIT), sublingual (SLIT), and epicutaneous immunotherapy (EPIT) with varying degrees of safety and efficacy. There are obvious advantages of treating food allergies with omalizumab, including less frequent administration (every 2 or 4 weeks) compared to the daily dosing of AITs, treating multiple food allergies with one medication, and the potential benefit for comorbid asthma and environmental allergies. However, disadvantages of omalizumab include the requirement for lifelong treatment of a costly biologic that will not induce immunologic tolerance. On the other hand, AITs have been shown to effectively induce desensitization in most individuals and can lead to long-term tolerance or remission in a subset of patients. In this review, we will discuss the pros and cons of omalizumab and AITs and the potential benefit of combining both approaches in young children to achieve immediate increases in reaction threshold while also inducing tolerogenic immunologic responses.